Hereditary Dystonia as a Neurodevelopmental Circuit Disorder: Evidence from Neuroimaging - Niethammer, Martin (2010)
Primary dystonia has traditionally been viewed as a basal ganglia disorder, but recent studies suggest that the cerebellum plays a crucial role in the disease. Primary dystonia is associated with several genotypes. Among those, DYT1 and DYT6 are inherited in autosomal dominant fashion with reduced penetrance. Extensive structural and functional imaging studies have been performed on manifesting and non-manifesting carriers of these mutations. The results suggest that primary dystonia can be viewed as a neurodevelopmental circuit disorder, involving the cortico-striato-pallido-thalamo-cortical and cerebello-thalamo-cortical pathways. Anatomical disruption of the cerebellar outflow is found in non-manifesting and manifesting mutation carriers, and a second downstream disruption in thalamo-cortical projections appears clinically protective in non-manifesting carriers. The microstructural deficits in cerebellar outflow are linked to an abnormally elevated sensorimotor network (NMRP) in dystonia patients. Abnormal expression of this network is reduced by successful treatment with deep brain stimulation.